2011
DOI: 10.5897/ajb10.401
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of orchid (Dendrobium nobile) var. Emma white

Abstract: Axillary buds of orchid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 17 publications
(22 reference statements)
2
11
0
Order By: Relevance
“…In addition, the application of cytokinins have been able to increase the number of shoots in orcid (Dendrobium nobile ISSN: 2414-4592 DOI: 10.20474/jater-2.4.4 TAF Publishing var. Emma white) which represents the importance of the exogenous cytokinin to promote the multiple shoots formation [27]. Similar to this study, the used of Kn has been able to produced plantlets of Oryza sativa L. Var.…”
Section: E Fresh and Dry Weightsupporting
confidence: 71%
“…In addition, the application of cytokinins have been able to increase the number of shoots in orcid (Dendrobium nobile ISSN: 2414-4592 DOI: 10.20474/jater-2.4.4 TAF Publishing var. Emma white) which represents the importance of the exogenous cytokinin to promote the multiple shoots formation [27]. Similar to this study, the used of Kn has been able to produced plantlets of Oryza sativa L. Var.…”
Section: E Fresh and Dry Weightsupporting
confidence: 71%
“…The highest number of roots per explant was found in the case of P. insigne cultivated in the presence of 2.5 mg•dm −3 IAA (3.3) in comparison to those grown on the medium supplemented with 5 mg•dm −3 NAA (2.2). A low number of roots after supplementation of the medium with NAA was also noted by Asghar et al [8] in Dendrobium nobile 'Emma White'. Additionally, the authors stated that the increasing concentration of the auxin seedlings produced fewer roots.…”
Section: The Paphiopedilum Insigne Rooting System In Vitro Depending supporting
confidence: 69%
“…Positive effects of IAA in a low concentration of 0.05 mg·dm −3 on the presence of roots was confirmed in the case of Geoderum purpureum [ 14 ], and in a concentration of 1 mg·dm −3 in Dendrobium transparent [ 33 ]. The reports of Asghar et al [ 8 ] proved the positive influence of IBA on the tested features. The authors demonstrated the desirability of the use of IBA in concentrations of 2 mg·dm −3 in Dendrobium nobile ‘Emma White’.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, discrete decreases were observed at concentrations above 0.5 mg L -1 BA for shoot dry matter. Contrasting results were observed by Asghar, Ahmad, Hafiz, and Yaseen (2011), who verified that BA concentrations up to 2.0 mg L -1 BA promoted significant increases in shoot dry matter of Dendrobium nobile var. Emma White.…”
Section: Effects Of Growth Regulators On Seedling Multiplication and ...mentioning
confidence: 65%